ANISOTROPIC SUPERCONDUCTING PROPERTIES OF ALIGNED (BI,PB)2CAN-1SR2CUNO2N+4+DELTA POWDERS (N = 1, 2, 3) WITH TC = 32, 94, AND 110 K - SHI, JB; CHIOU, BS; KU, HC (My University, 1991)
The anisotropic superconducting properties of aligned powders embedded in epoxy for bismuth copper oxides with the compositions (Bi1.6Pb0.4)(Sr1.5La0.5)CuO6+delta (n = 1, T(c) = 32 K), Bi2Ca1.2Sr1.8Cu2O8+delta (n = 2, T(c) = 94 K), and (Bi1.85Pb0.15)Ca2.2Sr1.8Cu3O10+delta (n = 3, T(c) = 110 K) are reported. These c-axis-aligned samples were prepared in a 9.4-T applied magnetic field at room temperature The temperature dependence of the anisotropy ratio chi-c(T)/chi-ab(T) in the superconducting state is derived from both zero-field-cooled and field-cooled data using a small applied field H (less than or equal to the lower critical field H(c1)) parallel and perpendicular to the orthorhombic c axis. A highly anisotropic chi-c/chi-ab ratio was observed for all three systems, the maximum value of chi-c/chi-ab = 9.8 at 5 K and 10.8 at 85 K for the 2:2:2:3 compound (Bi1.85Pb0.15)Ca2.2Sr1.8Cu3O10+delta was observed. The field dependence of the anisotropy ratio chi-c(H)/chi-ab(H) for the 2:1:2:2 compound Bi2Ca1.2Sr1.8Cu2O8+delta up to 5 kG is discussed.